Effect of heat treatment on the antioxidant activities of camel milk alpha, beta and total caseins: Antioxidant activities of camel milk caseins - Hamouda, Maha; Sboui, Amel; Salhi, Imed; omrani, Abir; Hammadi, Mohamed; Souchard, Jean Pierre; Bouajila, Jalloul; Khorchani, Touhami (Cellular and Molecular Biology, 2022)
This study aimed to evaluate the effect of various heating temperatures on the antioxidant activities of camel milk caseins. The samples were processed with three different heat treatments: Pasteurization at low and high temperatures and boiling. Fresh camel milk (unheated) was used as a control. Camel milk caseins were separated by fast ion exchange liquid chromatography (FPLC) and identified by the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS page). The antioxidant activities of caseins were measu- red by three different in vitro methods: 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, 2, 2’-azino-bis (3-ethylbenzthiazoline-6-sulfonate) (ABTS) radical scavenging activity and ferric reducing power assay (FRAP). The antioxidant activity evaluated by the DPPH assay decreased significantly (p<0.05) with the increase in heat treatment of caseins. However, there was no significant difference in ABTS radical scavenging activity and Ferric Reducing Antioxidant Power assay (FRAP) of heat-treated camel caseins compared to unheated onesStill, a decrease was observed in those activities by the increase of temperature in the different casein concentrations. Besides, whatever the concentration tested and the methods applied, the antioxidant activity of beta-casein (β−CN) was more pronounced than the alpha-casein (α-CN). Therefore, camel milk casein could be used as a natural source of antioxidants which may have a potential application in the food and nutraceutical industries. Throughout the different heat treatments applied, pasteurization at low temperature could be the most suitable alternative to preserve the antioxidant properties of camel milk.